Facile construction of nanoscale laminated Na3V2(PO4)3 for a high-performance sodium ion battery cathode. Issue 48 (29th November 2016) - Zheng, Qiong; Liu, Wanqiu; Li, Xianfeng; Zhang, Hongzhang; Feng, Kai; Zhang, Huamin
Abstract : A facile and economic construction of nanoscale laminated Na3 V2 (PO4 )3 for a high-performance sodium ion battery cathode is proposed. Abstract : A novel facile construction of nanoscale laminated Na3 V2 (PO4 )3 for a high-performance sodium ion battery (SIB) cathode is proposed. In the synthesis process, a crystallized intermediate precursor with low-cost raw materials is prepared by introducing a high temperature molten-state NH3 thermal-reduction process, which acts as a reaction template to control the crystal growth and the final morphology of Na3 V2 (PO4 )3 . The as-synthesized nanoscale laminated Na3 V2 (PO4 )3 possesses continuous Na + /electron pathways, large electrode/electrolyte contact area and sufficient carbon coating, resulting in fast Na + extraction/insertion and electron transport during the electrochemical reaction process, which is shown to achieve excellent rate capability and decent cycling stability. At a low rate of 0.5C, the discharge specific capacity is approximately 117 mA h g −1, which is very close to its theoretical specific capacity, and there is only a very minor capacity fade after continuous 250 cycles at 2C. Even at 50C, the discharge specific capacity is as high as 80 mA h g −1 and the reversible capacity retention after 3000 cycles remains more than 78%. In addition, the X-NVP cathode shows stable cycling performance and acceptable rate performance with a reversible capacity of 110 mA h g −1 at 0.2C at a low temperature of −20 °C, which has rarely been reported previously in the SIB field. The intermediate precursor prepared by the high temperature molten-state thermal-reduction method, acting as the reaction template of the final product, provides a facile and economic solution for the synthesis of high-performance SIB cathode materials.